Determination of low concentration of Paracoccus denitrificans encapsulated in polyvinyl alcohol LentiKat's pellets - Vacková, Lenka; Stloukal, Radek; Wanner, Jiří (Applied microbiology and biotechnology, 2012)
The aim of this work was to compare three methods to determinate low concentrations of Paracoccus denitrificans encapsulated in polyvinyl alcohol pellets, which is important for evaluation and optimization of pellet production as well as for monitoring of biomass growth. Pellets with different and well-defined biomass concentrations were used for experiments. The following fast and simple methods were tested: (1) dissolution of polyvinyl alcohol in hot water followed by dry weight estimation, (2) dissolution of polyvinyl alcohol in hot water followed by optical density measurement, (3) and extraction and quantification of proteins. Dry weight estimation proved to be problematic as it was difficult to separate biomass from polymeric carrier. Optical density measurement showed good linearity of dependence of optical density on biomass content, but determined limits of detection and limits of quantification were not within the range necessary for intended application. The only tested method meeting the requirements for sensitivity was determination of protein concentration after protein extraction.
Keywords: polyvinylalkohol; Paracoccus denitrificans; bakteriální nálož; Polyvinyl Alcohol; imobilizované buňky; Cells, Immobilized; Bacterial Load